Peace in Colombia - Calvo-Buezas, Tomás (Universidad Pedagógica y Tecnológica de Colombia, 2014)
The demand made by the Colombian country that becomes effective the signing of peace agreements between the Government and the FARC, the oldest Latin American guerrilla, awakens in the author of this article, the need for an invitation to build the peace that this country yearns. The author tells us the times when in one form or another there was understanding with the guerrillas, he speaks also of the people he met, which aroused in him the admiration and the need to fight for a just society; he speaks of the priest Camilo Torres, of Domingo Lain, José Antonio Jiménez and Manuel Pérez. It is therefore the main object of this author to reflect on the ideal of the guerrilla revolution. “Your ideals of justice were noble, but the means of armed violence was harmful and criminal".